2021
DOI: 10.1002/imhj.21937
|View full text |Cite
|
Sign up to set email alerts
|

Dual trajectories of parenting self‐efficacy and depressive symptoms in new, postpartum mothers and socioemotional adjustment in early childhood: A growth mixture model

Abstract: Postpartum depression and low parental self‐efficacy (PSE) are risk factors for poor child behavior. Little is known, however, about the course of dual trajectories of cooccurring depressive symptoms and PSE or its impact on children's socioemotional development. This study sought to identify trajectories of postpartum PSE and depressive symptoms in new, first‐time mothers using growth mixture modeling. Results demonstrated a class of women with “low risk” (88.8%) who manifested low levels of depression and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Two studies reported trajectories quantifying risk; the low-risk sample comprised approximately 90% of the study participants [ 88 , 89 ]. In addition, other trajectories identified in these two studies were: high-risk (persistent high depressive symptoms but below the cut-off for minor depression [ 88 ]; early risk (initially high severity of depression but declining over time) and late risk characterized by increasing depressive symptoms and decreasing parental self-efficacy throughout the study period [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported trajectories quantifying risk; the low-risk sample comprised approximately 90% of the study participants [ 88 , 89 ]. In addition, other trajectories identified in these two studies were: high-risk (persistent high depressive symptoms but below the cut-off for minor depression [ 88 ]; early risk (initially high severity of depression but declining over time) and late risk characterized by increasing depressive symptoms and decreasing parental self-efficacy throughout the study period [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment revealed these studies to be generally robust. However, 14 of the studies reported inadequate rates of attrition or missingness [ 37 , 76 78 , 80 , 81 , 83 , 85 , 86 , 88 , 89 , 93 95 ]. Only four of the studies [ 37 , 80 , 84 , 91 ] recruited participants which were representative of the general population.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to theory based interindividual phenotypes as in DSM, researchers have used growth mixture models and latent class trajectory models to empirically derive interindividual depression phenotypes that models between-person differences in symptom development. For instance, phenotypes have emerged in studies examining trajectories of depressive symptoms in those recovering from traumatic injuries (deRoon-Cassini et al, 2010), adolescent victims of cyberbullying (Hill et al, 2017), and postpartum mothers (Barboza & Schiamberg, 2021). A challenge with growth mixture models is that they assume the sample of interest is from a population that can be characterized by a single set of parameters (e.g., trend and baseline) that remain invariant across time (Ram & Grimm, 2009).…”
Section: Introductionmentioning
confidence: 99%